Letter of intent Pemerintah Indonesia kepada IMF. The political-economy of Int'l relations - DAHLAN, Harwanto (Univ Muhammadiyah Yogyakarta, 2000)
Letter of intent Pemerintah Indonesia kepada IMF. The political-economiy of int'l relations